The Austrian School in the thinking of Donald Stewart Jr. - Berlanza Corrêa, Lucas (2021)
This article is intended to synthesize the influence of the ideas and matrixes of the Austrian School of Economics in the thinking of Brazilian businessman and activist Donald Stewart Jr., offering an overview of the meaning of his performance to spread this line of thought in the country. Starting from a brief approach of his historically occupied position as an introducer of related literature and as the founder of the Liberal Institute, in 1983, the work will seek to connect this effort to the current popularity of Austrian authors in the country, showing how the entrepreneur and the institution he founded were decisive for this, and to expose Stewart's views, especially from his work What is Liberalism, about the contribution that this intellectual current could offer to the problems of the Brazilian reality.